KAPABILITAS ORGANISASI DINAS PERTANIAN TANAMAN PANGAN BAGI PENINGKATAN PRODUKSI KOMODITAS PADI DI KABUPATEN SUBANG TAHUN 2016-2018 - Suherlan, Suherlan; Sumaryana, Asep; Myrna, Rita; Adiwisastra, Josy (Jurnal Governansi, 2019)
The organizational capability of the Local Office of Agriculture and Food Plantation for improving the rice commodity production in Subang Regency year 2016-2018 had not been suitable yet with the plan of the Local Government of Subang Regency as regulated in the Local Regulation No. 14/2014 concerning the Local Middle Term Development Plan of Subang Regency Year 2014-2018 in order to increase the rice commodity production from 1.1 million ton to 1.6 million ton. The aim of this research is to describe the organizational capability of the Local Office of Agriculture and Food Plantation for improving the rice commodity production. The method of this research is descriptive. This research uses the primary and secondary data. The data of this research is qualitatively analyzed. The results of this research indicate that the organizational capability for improving the rice commodity production could not develop the new irrigation and optimize the rice field land yet. Moreover, the rice plantation time planned three times a year was not achieved because of the lack of water supply. Consequently, the achievement of rice commodity production in last 2018 was only 1.3 million ton. The knowledge and skills of the civil servants at field could not be practiced yet. The organizational capability had not been suitable yet with the program of irrigation reconstruction and the supporting infrastructures. Therefore, the Local Office of Agriculture and Food Plantation and other local organizations related to the agricultural sector had not optimally co-operated yet. Keywords: Organizational Capability, Rice Commodity, Agriculture and Food Plantation.